Prevalence of Chlamydia trachomatis: results from the first national population-based survey in France - Goulet, V; de Barbeyrac, B; Raherison, S; Prudhomme, M; Semaille, C; Warszawski, J (Sexually transmitted infections, 2010)
BackgroundFew studies have estimated Chlamydia trachomatis (CT) prevalence in the general population, most prevalence studies being based on people already attending healthcare settings.ObjectivesTo estimate the prevalence of CT in France, assess the feasibility of home sampling without any face-to-face intervention and identify risk factors associated with CT infection using data from the Contexte de la Sexualité (CSF) survey on sexual behaviour; a national population-based survey, carried out by telephone in 2006.MethodsA random subsample of sexually experienced people aged 18–44 (N=4957) were invited to participate in a CT home-sampling study (NatChla study). Participants' samples were tested for CT by PCR. Percentages were weighted for unequal selection probabilities and post-stratified based on French population census data. Independent risk factors were identified by logistic regression.ResultsCT prevalence in people aged 18–44 was estimated at 1.4% (95% CI 0.8% to 2.6%) for men, and 1.6% (95% CI 1.0% to 2.5%) for women. Increased rates were found in subjects aged 18–29: 2.5% (95% CI 1.2% to 5.0%) for men and 3.2% (95% CI 2.0% to 5.3%) for women. CT infection was associated, for both genders, with having their last sexual intercourse with a casual partner. Other risk factors were for men, having last intercourse with a new partner, living in the Paris area, and for women, multiple partners during the previous year, same sex partners and a low level of education.ConclusionsCT prevalence in France is similar to that in other developed countries. Home sampling proved feasible and useful to reach members of the population with limited access to traditional care.